Polycomb epigenetic mechanisms: methylation of DNA - Pirrotta, Vincenzo (Henry Stewart Talks, 2007)
PRC2 has an untargeted global function, Chromatin immunoprecipitation (ChIP-seq) profiles, H3K27 methylation, The CBP/p300 acetylase complex, The TRR complex (MLL3,4 in mammals), The DNA accessibility model, How do PcG complexes repress?, The essential role of canonical PRC1, Links between PRC1 and PRC2, The bivalent state
Updated at 2017/12/31